New highlights on effects of rapid palatal expansion on the skull base: a finite element analysis study - SEVILLANO,Manuel Gustavo Chávez (2021)
ABSTRACT Objective: The objective of this study was to evaluate the effect of the rapid palatal expansion (RPE) on the pterygoid process (PP), spheno-occipital synchondrosis (SOS) and sella turcica (ST) in the skull of a patient with transversal maxillary collapse, and identify the distribution of mechanical stresses and displacement, by finite element analysis (FEA). Methods: Cone-beam computed tomography (CBCT) was employed to examine the skull of a patient in this study. The patient was a 13-year-old boy, with Class II skeletal relationship due to transverse atresia and maxillary protrusion. The computer-aided design (CAD) geometry of skull was imported into the SimLab v. 13.1 software, to build the finite element mesh. For the simulation, a displacement of 1 mm, 3 mm and 5 mm in a transverse direction was defined at the midpalatal suture, thereby representing the RPE. For the analysis of results, maximum principal stress (MPS) and displacements were evaluated by identifying different nodes, which were represented by the points as per the areas of interest in the study. Results: In MPS, the maximum tensile stress was found at point 2 (366.50 MPa) and point 3 (271.50 Mpa). The maximum compressive stress was found at point 8 (-5.84 Mpa). The higher displacements in the transversal plane and the lateral segment were located at point 1 (2.212 mm), point 2 (0.903 mm) and point 3 (0.238 mm). Conclusions: RPE has a direct effect on PP, SOS and ST in the Class II model skeletal relationship with a transversal maxillary collapse. PP supported a higher tensile stress and displacement.